Stability and Wash Resistance of Local Made Mosquito Bednets and Detergents Treated with Pyrethroids against Anopheles stephensi - H Vatandoost; E Ramin; Y Rassi; MR Abai (Tehran University of Medical Sciences, 2009)
Background: We aimed to evaluate different fibres of bednets impregnated with various pyrethroids. The stability of insecticide on the bednet was measured using different methods of washings as well as local made detergents. Methods: The entire test was carried out according to the WHO-recommended methods. In addition, the impact of the numbers of washes on the stability of the insecticides was determined. Permethrin 10% (EC), deltamethrin 10% (SC), lambdacyhalothrin 2.5% (CS) and cyfluthrin 5% (EW) were used at the recommended dosages. Three different local detergents were used. Two kinds of washing methods (shaking, no shaking) were used and in each method four kinds of washings, i.e. no wash, one wash, two washes and three washes was done. The main malaria vectors, Anopheles stephensi, which is susceptible to all insecticides (BEECH strain), was tested with impregnated bednets in 3 minutes exposure time and the mortality was measured after 24 hours recovery period. Knock-down was measured as well using appropriate statistical methods. Results: Lambdacyhalothrin has saved its insecticidal impact after being washed, whereas, deltamethrin has lost its activity faster than other insecticides. Tow other insecticides had moderate effect. Golnar soap detergent has least effect on the durability of insecticides, but the Shoma had the most. Whit increasing  the times of washing, insecticidal effects was decreased , but shaking had no influence on the decreasing  of the quality of insecticidal impact. Conclusion: Results will be useful for local people who wish to use pyrethroid-impregnated bednets with their own local made detergent and bednets.